Female and male-controlled livestock holdings impact pastoralist food security and women's dietary diversity - H. Gitungwa; C. R. Gustafson; E. Y. Jimenez; E. W. Peterson; M. Mwanzalila; A. Makweta; E. Komba; R. R. Kazwala; J. A. K. Mazet; E. VanWormer (BMC, 2021)
Abstract Background Food insecurity is a global problem that requires a One Health approach. As many households in low- and middle-income nations rely on crops and livestock that they produce to meet their household's needs, food security and nutrition are closely linked to the health of animals and the environment. Resources controlled by women are more often allocated to uses that benefit the entire household, such as food, health, and educating children, than men's resources. However, studies of gender control of resources among pastoralist societies are scant. We examined the effect of female and male control of livestock resources on food security and women's dietary diversity among households from one agro-pastoralist and two pastoralist tribes in Iringa Region in south-central Tanzania. Methods We conducted surveys with 196 households, which included questions on food availability and food consumption among women, livestock holdings, gender control of livestock and livestock product income, and household demographics, as well as open-ended questions on the use of income. Food availability and food consumption responses were used to construct food security and women's dietary diversity indexes, respectively. We conducted mixed effects logistic regression to analyze how household food security and dietary diversity were associated with livestock and other household variables. We also examined qualitative responses for use of income controlled by women and how the household obtained income when needed. Results Female-controlled livestock generally supported better household nutrition outcomes. Greater chicken holdings increased the probability of being food secure in pastoralist households but decreased it in agro-pastoralist households, while increasing the probability of having medium-high dietary diversity among all tribes. Male-controlled livestock holdings were not related to food security status. Women used income to supplement food supplies and livestock they controlled as a primary response to unanticipated household needs. Conclusions Our results show that female-control of livestock is significantly related to household food security and dietary diversity in pastoralists and agro-pastoralists in rural Tanzania. Importantly, the relationship between food security and dietary diversity differs among tribes for both male and female-controlled livestock, which suggests that blanket policies regarding management of livestock holdings may have unintended consequences.